Clinical-epidemiologic profile of elderly with Aids - Sousa, Ana Carla A.; Suassuna, Daniella S.B.; Costa, Stênio Melo Lins da (Brazilian Journal of Sexually Transmitted Diseases, 2009)
Introduction: analyzing the evolution of aids among the elderly through the description of epidemiologic characteristics of infected people will contribute to the adoption of public politics to face this problem. Objective: analysing the epidemiologic profile from the elderly in the of city João Pessoa, Paraiba. Methods: descriptive epidemiologic research based on secondary source of data. Results: the population was formed by patientes aged above 59 years old, who attended the Complexo Hospitalar Clementino Fraga (CHCF) between January 1st, 2004 and February 28th, 2008. The data had been obtained from handbooks of patients and from consultation to SINANW and SINAN NET databasis. The investigated variables were: age group, gender, educational level, origin, marital states, category of exhibition, use of preservative, type of parcery and deaths. The data were analysed through the evaluation of difference in percentages. Results: male gender was majority in the sample corresponding to 55% of cases; 89% of women and 54,55% of men were declared heterosexuals; among women, 66,67% was maintaining sexual relations with partners infected by HIV, 22,2% were not using preservative, the majority had low educational levels and proceeded from cities from countryside; among the men, 36,37% were maintaining sexual relations with multiples partners, the majority was formed by singles with low degree of education and originating from cities of the countryside. Conclusion: the population in general, both men and women, was characterized by heterosexuality, low degree of education and origin, results that demonstrate the current tendency of the epidemic in heterossexual, poor and countryside inhabitants process. The high percentage of women maintaining relationships with soropositives and the relative percentage that was not using preservative demonstrated the necessity of the intensification of educational actions to prevent the aids through increasing awareness of the necessity of the use the preservatives in the heterosexual relations